Crystal phase-controlled synthesis of rod-shaped AgInTe2 nanocrystals for in vivo imaging in the near-infrared wavelength region. Issue 10 (22nd February 2016) - Kameyama, Tatsuya; Ishigami, Yujiro; Yukawa, Hiroshi; Shimada, Taisuke; Baba, Yoshinobu; Ishikawa, Tetsuya; Kuwabata, Susumu; Torimoto, Tsukasa
Abstract : Rod-shaped AgInTe2 nanocrystals exhibiting intense photoluminescence in the near-infrared wavelength region were successfully prepared and applied to in vivo imaging. Abstract : Rod-shaped AgInTe2 nanocrystals (NCs) exhibiting intense near-band edge photoluminescence in the near-infrared (NIR) wavelength region, were successfully prepared by the thermal reaction of metal acetates and Te precursors in 1-dodecanethiol. Increasing the reaction temperature resulted in the formation of larger AgInTe2 NCs with crystal structures varying from hexagonal to tetragonal at reaction temperatures of 280 °C or higher. The energy gap was increased from 1.13 to 1.20 eV with a decrease in rod width from 8.3 to 5.6 nm, accompanied by a blue shift in the photoluminescence (PL) peak wavelength from 1097 to 1033 nm. The optimal PL quantum yield was approximately 18% for AgInTe2 NCs with rod widths of 5.6 nm. The applicability of AgInTe2 NCs as a NIR-emitting material for in vivo biological imaging was examined by injecting AgInTe2 NC-incorporated liposomes into the back of a C57BL/6 mouse, followed by in vivo photoluminescence imaging in the NIR region.